Influence of local and systemic antibiotics in peri-implantitis treatment : a systematic review - Estácio, Catarina Batista Pires da Costa (2023)
Background: This systematic review (SR) aimed to synthesize what is known about local and systemic antibiotics effectiveness in treating peri-implantitis. (Page et al., 2021) Material and methods: This SR is reported in compliance with the PRISMA statement. The review protocol was registered into the PROSPERO database (CRD4202238040) (Page et al., 2021) Results: The analysis included ten randomized controlled trials (RCTs) with follow-ups ranging from 3 to 12 months. No implant loss occurred during the study's follow-up periods. Probing pocket depth (PPD) reduction across the studies varied from 0.00 to 3.82 mm, while bleeding on probing (BOP) resolution ranged from 1.02% to 51.0%. Interestingly, certain trends emerged when the effects of local antibiotics were compared to those of systemic antibiotics. Compared to local antibiotics, systemic antibiotics appeared to result in greater reductions in probing pocket depth (PPD) and bleeding on probing (BOP), suggesting that systemic antibiotics may significantly improve periimplant tissue health and lower inflammation. Conclusions: Non-surgical antibiotic treatment (both systemic and local) improves periimplant tissue health, lowering PPD and BOP. Complete pocket resolution, on the other hand, is not guaranteed. While systemic antibiotics are useful, they must be used with caution due to various patient circumstances.